A posição do gen Y3 no cromossomo 2 do milho - Graner, E. A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1952)
This paper deals with the genetic relations among y3 - lg1 - gl2. The data obtained indicate the relative order in chromosome 2 as follows: y3 7 gl1 18 gl2.